The Entanglement between Religion and Politics: Hong Kong Christianity in the Anti-Extradition Bill Movement - Xing, Fuzeng (Review of Religion and Chinese Society, 2021)
Abstract The relationship between religion and social movements is an important topic in the study of religion and society. This paper uses various textual and online sources to examine the role of Christianity in the anti-extradition bill movement that took place in Hong Kong from April to September 2019. The anti-extradition bill movement, which later evolved into a much wider movement against totalitarianism, has caused churches to grapple with church-state relations in the post-handover era. This paper employs the notion of “public religion” as an analytical framework to examine the process of the “deprivatization” of Christianity in Hong Kong. How does the ongoing contestation, both within and outside the church, reflect the challenges faced by Christianity when entering the public sphere? By answering the above questions, we will be able to explicate the religio-political significance of the protest movement in Hong Kong.